Dampak Terjadinya Stunting terhadap Perkembangan Kognitif Anak : Literature Review - Rakhmalia Imeldawati (Jurnal Medika Nusantara, 2025)
Stunting, a growth disorder in young children caused by chronic malnutrition, can significantly impair a child's growth and development, especially cognitive development. This paper reviews the scientific evidence linking to cognitive delay. The author uses data from reference journal articles and several theories published between 2019 and 2024 accessed through Google Scholar, PubMed, Scopus, NCBI, and others using keywords such as "stunting", "nutritional status", and "cognitive development". The findings of the assessment demonstrated a clear association between stunting and cognitive development in children. Stunting children are at higher risk of experiencing impaired cognitive development compared to non-stunted children. Untreated cognitive development can affect the quality of life of the individual in the future. Therefore, appropriate intervention programs are needed to address stunting.